Effects of Cordyceps militaris solid medium on the growth performance, immunity parameters and intestinal health of broilers - Xiaoya Wang; Jingyan Zhang; Kang Zhang; Guowei Xu; Zhiting Guo; Xueyan Gu; Saad Ahmad; Liping Huang; Shuqi Liu; Jianxi Li; Lei Wang (Animal Bioscience, 2025)
Objective This study aimed to investigate the impact of Cordyceps militaris solid medium (CMM) on the growth performance, immunity parameters, intestinal health and gut microbiota of broilers. Methods A total of 320 male broilers were randomly allocated into 4 groups, consisting of 8 replicates and 10 birds per replication. The broilers were fed diets comprising the Control group, 0.02% CMM group (Low CMM), 0.2% CMM group (Mid CMM), or 2% CMM group (High CMM). Samples were collected on 14d and 28d of the experiment. Serum was collected for the determination of biochemical indices and immunoglobulins, the intestinal morphology of the duodenum, jejunum and ileum was observed, and cecum contents were collected for 16S rRNA gene sequencing. Results Over the course of the 28d trial, the broilers fed CMM had a higher average daily gain and lower feed conversion rate than the control broilers at Days 14 and 28. Notably, compared with those of the Control group, the Low CMM diet increased the thymus and bursa indices significantly (p<0.05). Enzyme-linked immunosorbent assay revealed that CMM increased the IgA, IgM, and IgG levels in the serum, and the IgA level in the Low and Mid CMM groups was significantly higher than that in the Control group (p<0.05). A Low CMM diet showed the strongest ability to increase villus height (VH) and villus height/crypt depth, and CMM affected the relative mRNA expression levels of inflammatory factors in jejunal tissue. The 16S rRNA results showed that the CMM group presented a greater relative abundance of Firmicutes and a higher Firmicutes/Bacteroidetes ratio than did the Control group at 14 d and 28 d, and the Deferribacteres abundance also increased (14 d). At the genus level, a Low CMM diet decreased Bacteroides abundance (p<0.05) but increased the abundance of Synergistetes (p>0.05). Conclusion These results illustrate that 0.02% CMM in the diet can promote growth performance, increase immunity, improve intestinal morphology, and regulate the intestinal flora of broilers.